Cover Image, Volume 9, Issue 1. (20th December 2018) - Wang, Yu‐Chen; Ke, Yaling; Zhao, Yi
Abstract : The cover image is based on the Advanced Review The hierarchical and perturbative forms of stochastic Schrödinger equations and their applications to carrier dynamics in organic materials by Yi Zhao et al., DOI: 10.1002/wcms.1375 . Abstract : The cover image is based on the Advanced Review The hierarchical and perturbative forms of stochastic Schrödinger equations and their applications to carrier dynamics in organic materials by Yi Zhao et al., DOI: 10.1002/wcms.1375 .